Antibodies in horses, mules and donkeys following monovalent vaccination against African horse sickness. - Hamblin, C. (Cambridge University Press, 1991)
A total of 256 sera collected from three species of domesticated equidae in four different Spanish provinces were examined 1-4 months after the administration of attenuated monovalent African horse sickness virus (AHSV) serotype 4 vaccine. Approximately 10% of the sera were negative by ELISA, virus neutralization, agar gel immuno-diffusion and complement fixation tests. Similar negative reactions were recorded with sera from two ponies after experimental primary vaccination. The rapid rise in antibodies in sera from these two ponies, after a second dose of vaccine, suggested they would probably have been immune to challenge. It is therefore suggested that the apparent absence of antibodies against AHSV in some animals after primary vaccination may not necessarily indicate a total lack of protection.